Stock analysis of peacock bass (Cichla spp) marketed in the fishing market of Porto Velho (Rondônia) (Research, Society and Development, 2022)
In the Amazon region the Peacock Bass (Cichla spp) is highly appreciated in commercial and sport fishing, so understanding its biological characteristics is essential for the management and conservation of the species. This work aimed to analyze the situation of the stock and fishing dynamics of peacock bass, marketed in the fishing market of Porto Velho (Rondônia), in the period from 2011 to 2020. Growth rates (length of and weight) identified the stock indicators and parameters. The inventory indicators show that the years 2011 and 2017 presented higher values in the age of first maturation, with an average of 20%, 2013 presents a better capture, being 7.6% at the age of first maturation, only the years 2012, 2013 and 2017 were with the percentages of ideal capture (Popt), being 60, 79 and 69% respectively, where the reference values are 60 to 80%, but the inventory indicator (Pobj) showed overfishing in all years, standing out in 2011 and 2018 with the highest overfishing rate. The results indicate that peacock bass, in the study region are overfished, what require fishing monitoring and management aiming at the protection of the stock.